Online information use on health/illness by relatives of hospitalized premature infants - Vanessa Ferreira de Lima; Verônica de Azevedo Mazza; Carmen Gracinda Silvan Scochi; Luciana Schleder Gonçalves
ABSTRACT Objective: To analyze the use of online information on health/illness by relatives of premature infants admitted to the Neonatal Intensive Care Unit. Method: Exploratory, qualitative study conducted at a Neonatal Intensive Care Unit from a University Hospital in the state capital of southern Brazil, with 33 relatives of hospitalized premature infants. The data were collected through a semi-structured interview and were submitted to thematic analysis, with the aid of the software Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires (IRAMUTEQ®). Results: From the data analysis, two thematic categories emerged: Online information on health/illness researched by relatives; and Online sources of information consulted by relatives. Final considerations: Health professionals need to consider the use of online information by relatives in the care process, adding it in their practice in relation to the informational needs presented, and stimulating spaces for dialogue about the data found.